Quadrupolar Ion Excitation for Radiofrequency-Only Mass Filter Operation. Issue 3 (June 2014) - Douglas, Don J.; Polyakov, A.; Konenkov, Nikolai V.
Trajectory calculations are used to model a mass filter based on the radiofrequency (rf)-only operation of a linear quadrupole with resonant quadrupole excitation of ions (resonant excitation applied with the same spatial electric field as the main quadrupole rf field). Ions are not trapped, but pass continuously through the quadrupole. Excited ions gain axial kinetic energy in the fringe field at the quadrupole exit, overcome a stopping potential and are transmitted to an external detector. No quadrupole direct current is required, unlike conventional operation at the tip of the first stability diagram. Quadrupole excitation can be applied with amplitude or frequency modulation of the main rf voltage, or with an auxiliary excitation voltage. All three methods give the same mass resolution. The mass resolution, R, is given by R ≈ 0.5 q (dβ/d q ) n where q is a Mathieu parameter, β( q ), determines the frequency of ion oscillation and n is the number of cycles of the rf field experienced by an ion, determined by the flight time through the quadrupole. A disadvantage of this mode of operation is that the flight times of the ions and the excitation amplitudes or modulation depths need to be synchronized.